Psychology - Cardwell, Mike (Longman A and AS-level revise guides, 1994)
Contains a syllabus breakdown and analysis. There is examiner commentary throughout plus exam questions and specimen answers. Typical student's answers with examiner's opinion and comments are included. There are also pull-out review sheets at the end of most topic-based chapters.